Logistics education and behavioral training decisions, time distortion, and the prae ante view - Thomas Neukirchen; Matthias Klumpp (Logistics, 2018)
In training and education for logistics, time inconsistency affects individual decisions regarding education and career choices. This is especially relevant in view of growing boundarylessness of careers that impacts the logistics sector with its high ratio of lateral entrants. We enrich the analysis of training and education decision-making processes with a third view beyond the common ex ante and ex post perspectives that has not been employed yet in this context. Our insights, modeled as a new prae ante view, can help prevent myopia in educational choice on an individual level and the resulting economic inefficiencies. This translates into more fitting provisions by individuals earlier, and into improved targeting of prospective employees in logistics. The purpose of this study is to provide an agent-based description grounded in behavioral economics, supported by an explorative empirical survey using extensive semi-structured expert-interviews with six participants concerning four to six career transitions each, conducted with employees in logistics professions. Main conclusions include that participants who were asked openly about influential factors for education and career decisions were oblivious of some factors described as highly predictive of educational and career success in literature, not acknowledging social and cultural capital, habitus, and chance, but also consistently ascribing success to a “milestone-mindset” to be described here as well.
Keywords: 650; information acquisition; logistics education; logistics training; prae ante; time inconsistency; vocational decision-making